2021
DOI: 10.3389/fvets.2021.597630
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Basic Reproduction Numbers of the Subtypes H5N1, H5N8, and H5N6 During the Highly Pathogenic Avian Influenza Epidemic Spread Between Farms

Abstract: It is important to understand pathogen transmissibility in a population to establish an effective disease prevention policy. The basic reproduction number (R0) is an epidemiologic parameter for understanding the characterization of disease and its dynamics in a population. We aimed to estimate the R0 of the highly pathogenic avian influenza (HPAI) subtypes H5N1, H5N8, and H5N6, which were associated with nine outbreaks in Korea between 2003 and 2018, to understand the epidemic transmission of each subtype. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…An experimental study of HPAI H5N6 has provided evidence of different likelihoods of transmission from wild birds to ducks or chickens, with the results suggesting a more efficient transmission from wild birds to ducks than to chickens (Seekings et al., 2021). Furthermore, the previous HPAI epidemiological study in South Korea suggested that the species specificity of HPAIV contributes to transmission dynamics (W. H. Kim & Cho, 2021). Our findings suggest that it has different epidemiological characteristics depending on the species raised on the farm, implying that different biosecurity measures are required.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An experimental study of HPAI H5N6 has provided evidence of different likelihoods of transmission from wild birds to ducks or chickens, with the results suggesting a more efficient transmission from wild birds to ducks than to chickens (Seekings et al., 2021). Furthermore, the previous HPAI epidemiological study in South Korea suggested that the species specificity of HPAIV contributes to transmission dynamics (W. H. Kim & Cho, 2021). Our findings suggest that it has different epidemiological characteristics depending on the species raised on the farm, implying that different biosecurity measures are required.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical samples are transferred to the provincial centre for pathological examination and confirmatory diagnostic testing by RT‐PCR for the presence of the H5 and H7 subtypes of avian influenza. For RT‐PCR as definitive diagnostic testing including identification of the N subtype, the sample is transferred to the Animal and Plant Quarantine Agency (W. H. Kim & Cho, 2021). The other reporting source for HPAI‐positive farms was from contact tracing by the provincial veterinary service centre.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated when HPAI H5N1 clade 2.3.4.4b were introduced into dairy cattle under a Bayesian framework in BEAST v.1.10.4 ( 71 ) with the BEAGLE library ( 72, 73 ). We merged the subsampled public data with newly generated whole genome data and aligned the hemagglutinin dataset (n=606 HA genes).…”
Section: Methodsmentioning
confidence: 99%
“…To reconstruct the spatial diffusion of the H5N1 virus across states within the US and different hosts (poultry, wild bird, cattle, mammal, domestic mammal, and humans), we applied an asymmetric discrete-trait phylogeographic analyses with Bayesian stochastic search variable selection, a strict molecular clock, and an exponential growth model in BEAST v.1.10.4 ( 71 ). We conducted this analysis on the subsampled and aligned hemagglutinin dataset and an extracted the monophyletic clade of cattle HA clade 2.3.4.4b genes with any host category (host) or cattle only (location).…”
Section: Methodsmentioning
confidence: 99%